Examining the perceived versus the actual knowledge about forensic odontology: A cross‐sectional survey among dentists. Issue 6 (13th December 2018) - Almutairi, Adel F.; Alkhtheri, Bayan A.; Aleidan, Hattan N.; Alhabib, Asma A.; Alotaibi, Eid A.; Salam, Mahmoud
Abstract: Dentists should have the basic essential skills and knowledge about forensic odontology, to better collaborate with law enforcement and investigations. The objective of this survey was to assess the perceived and actual knowledge toward forensic odontology among dentists and to question their willingness to attend training courses on this specialty. A cross‐sectional survey based on a self‐administered questionnaire was conducted in various districts of Saudi Arabia. Four hundred dentists responded to a questionnaire that tested their actual knowledge of forensic odontology based on answering 15 statements using the alternatives correct, incorrect, do not know. The perceived knowledge was registered as strongly agree, agree, neutral, disagree, and strongly disagree, then assigned scores respectively from four to zero. A willingness to attend a training course in the future was recorded by (yes/no). Scores were summated then subjected to descriptive statistics and regression analyses. Responses were received from 360 study participants (89% response rate). The percentage of correct answers, that is, the actual knowledge, was 67.9 (standard deviation [ SD ] ± 18.4). About two thirds of the responders ( n  = 251, 69.7%) indicated a willingness to attend a forensic odontology course in the future. Differences in both actual and perceived knowledge were identified on the basis of gender, work experience, education level, attended a course in forensic odontology, and having previously provided a past bite‐mark examination. The perceived knowledge on forensic odontology among dentists was moderate to low. The gap between perceived and actual knowledge signifies low self‐confidence. Dentists with higher education levels and experience tend to have better knowledge.